1987
DOI: 10.1111/j.1365-2141.1987.tb02352.x
|View full text |Cite
|
Sign up to set email alerts
|

α, β and γ T-cell receptor genes: rearrangements correlate with haematological phenotype in T cell leukaemias

Abstract: We have studied the arrangement of the alpha, beta and gamma T cell receptor (TCR) genes in 27 patients with T cell lymphoproliferative disorders. Nine patients had acute lymphoblastic leukaemia (T-ALL), nine patients had prolymphocytic leukaemia (PLL), six patients presented with a T-CLL/T-lymphocytosis syndrome, two patients had Sezary syndrome (SS) and one patient had HTLV-I positive T-cell leukaemia/lymphoma (ATLL). alpha TCR gene rearrangement could be demonstrated by the use of three available probes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…It is well known that TCR-[5 rearrangement can be demonstrat ed in the majority of cases with T-cell malignancies [26,27] including ATL [28]. However, Matsuoka et al [28] concluded that the nucleotide sequence analyses of Vp genes did not support the receptor-mediated leukaemogenesis theory for ATL.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that TCR-[5 rearrangement can be demonstrat ed in the majority of cases with T-cell malignancies [26,27] including ATL [28]. However, Matsuoka et al [28] concluded that the nucleotide sequence analyses of Vp genes did not support the receptor-mediated leukaemogenesis theory for ATL.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was prepared from whole blood or Epstein-Barr virus-transformed lymphocytes (14). Phage A genomic libraries were constructed from this DNA after it had been digested with HindIll or EcoRI and size-fractionated on 0.5% agarose gels or 10-40% sucrose gradients.…”
Section: Methodsmentioning
confidence: 99%
“…Hepatosplenomegaly was noticed on physical examination. Laboratory data showed a hemoglobin of 10.8 g/dl, hematocrit 35.8570, and leukocyte count 178 X 109/1 with the differential typical of chronic myelogenous leukemia. A nuclear liver/spleen scan revealed splenomegaly and a probable splenic infarct.…”
Section: Case Reportmentioning
confidence: 98%